Influence Substitution of Tabas Stone Waste which Coated Polyester Resin to Concrete Compressive Strength - Astariani, Ni Kadek; Eka Partama, I Gusti Ngurah; Dwi, I Gusti Ayu R Cahri Setia (ASTONJADRO, 2023)
The need for the use of concrete raw materials is increasing in line with the increase in the use of concrete in construction. The availability of concrete raw materials is dominated by the exploitation of natural resources, namely components of cement, sand and crushed stone or gravel. If the availability of this material is exploited in excess, it will have an impact on environmental damage. On the other hand, many stone crafts for decoration and building ornaments in Bali also utilize tabas stone which is also exploited from nature, where the processed rock leaves a lot of waste that is disposed of without any wise processing actions. Tabas stone waste management is expected to maximize the utilization of natural resources and also reduce environmental pollution caused by the disposal of tabas stone waste that is not managed properly. This research is expected to provide an alternative to maximize the use of tabas waste as a partial substitution of crushed stone or gravel as coarse aggregate in concrete mixtures. The porous structure of tabas stone and the high level of water absorption in the concrete mix can reduce the compressive strength of the concrete. Steps to reduce water absorption in tabas stone are carried out by maximally closing the pores using a polyester resin coating. The study was carried out by making normal concrete mixture objects according to SNI 03-2834-2000. The percentage of substitution of crushed stone with waste stone that is coated with polyester resin is 0%, 25%, 50%, 75%, 100% of the required weight of coarse aggregate. The compressive strength of the concrete will be tested at the age of 7 and 28 days using a cylindrical specimen measuring 150x300mm. Test results in the laboratory showed that the coating of tabas stone using polyester resin was able to reduce the level of water absorption from 9.96% to 3.24% or 67.5% compared to tabas stone that was not coated with polyester resin. The optimum compressive strength of coarse aggregate substitution using tabas was obtained at variations of 50% crushed stone 50% tabas stone at the age of 7 days and 28 days, respectively, reaching 15.06 MPa and 21.55 MPa.